Functional characterization of DYRK1A missense variants associated with a syndromic form of intellectual deficiency and autism - Widowati, Esti Wahyu (Biol Open, 2018)
Haploinsufficiency of DYRK1A is a cause of a neurodevelopmental syndrome termed mental retardation autosomal dominant 7 (MRD7). Several truncation mutations, microdeletions and missense variants have been identified and result in a recognizable phenotypic profile, including microcephaly, intellectual disability, epileptic seizures, autism spectrum disorder and language delay. DYRK1A is an evolutionary conserved protein kinase which achieves full catalytic activity through tyrosine autophosphorylation. We used a heterologous mammalian expression system to explore the functional characteristics of pathogenic missense variants that affect the catalytic domain of DYRK1A. Four of the substitutions eliminated tyrosine autophosphorylation (L245R, F308V, S311F, S346P), indicating that these variants lacked kinase activity. Tyrosine phosphorylation of DYRK1A-L295F in mammalian cells was comparable to wild type, although the mutant showed lower catalytic activity and reduced thermodynamic stability in cellular thermal shift assays. In addition, we observed that one variant (DYRK1A-T588N) with a mutation outside the catalytic domain did not differ from wild-type DYRK1A in tyrosine autophosphorylation, catalytic activity or subcellular localization. These results suggest that the pathogenic missense variants in the catalytic domain of DYRK1A impair enzymatic function by affecting catalytic residues or by compromising the structural integrity of the kinase domain. This article has an associated First Person interview with the first author of the paper.